John Smith's Decision To Make A Better Life In D.J. Caruso's I Am Number Four Movie (2011): An Individual Psychological Approach - Najmusysyarqi, Najmusysyarqi; , Drs. Abdillah Nugroho, M.Hum; , Titis Setyabudi, S.S., M.Hum (2013)
The major problem of this study is how decision to make a better life in I am Number Four movie based on individual psychological approach is. This study analyzes the structural elements in I am Number Four movie and John Smith's decision to make a better life based on individual psychological point of view. In analyzing the movie, the researcher uses qualitative study. The object of the study is John Smith. The primary data is I am Number Four movie itself. The secondary data are script of the movie and internet websites related to the study. The method of collecting data is purpose sampling by watching carefully the movie and then the researcher tooksample dialogue and picture of the movie then used them as a starting point to analyze the issue. The technique of data analysis is descriptive technique. The result of the analysis shows the following conclusion: first, John Smith chooses to get better life without moving, running, and hiding again. He becomes more optimistic and independent for his life. Second, John Smith chooses to surpass his problem through his action. He has the courage to fight the Mogadorians enemy. He searches the other Lorienbecause they are stronger iftogether.